Nothing but medals? Attitudes towards the importance of Olympic success - Haut, J.; Prohl, R.; Emrich, E. (International Review for the Sociology of Sport, 2016)
States intervene increasingly in financing and organization of Olympic elite sport in order to maximize national success in the medal table. In Germany and many other countries too that includes practices that have been criticized as unacceptable in democratic societies: funding of medal-promising sports only, early selection and specialization of young athletes, authoritarian tendencies in sport policy, etc. Are those efforts reflected by a strong desire for medals within the population? Is national success regarded as so important that even critical measures are accepted? And would that indicate more general tendencies to nationalistic or authoritarian attitudes? These and other questions were addressed in a survey carried out in Germany in 2012 (N = 899). Results show that medals are indeed perceived as important, especially in lower educational levels, but by far not as important as sticking to sporting values and the rules of fair play. Multivariate analyses reveal that the desire for medal success is highly dependent on the belief in and perception of the Olympic competition. For most of the respondents that does not legitimize unfair practices or exploiting athletes, but partly the struggle for medals is also linked with a limited understanding of fair play and nationalistic or authoritarian attitudes.